RISIKO KEBANGKRUTAN, PROPORSI HUTANG DAN FENOMENA UNDERPRICINGPADA IPO: STUDI EMPIRIS DI BURSA EFEK INDONESIA - Andreas Arif Kristanto (Jurnal Riset Manajemen dan Bisnis, 2012)
The purpose of this study is to examine the effect of bankruptcy risk and debt proportion to undepricing phenomenon in Initial Public Offering. This study analyzes a sample of initial public offfering made of indonesian stock exchange-listed non finance firms over the periode 2001-2010. Date analysis uses multiple regression model. The results show that debt proportion have negative effect on underpricing, while bankruptcy risk shows no such effect. This result consistent with signaling equilibrium phenomenom.Keyswords: underpricing, debt, and bankruptcy risk.